Petit traité montrant que c’est que doit faire un homme fidèle connaissant la vérité de l’Evangile, quand il est entre les papistes (1543) : Jean Calvin et les nicodémites - Vincent Parello (Les Cahiers de Framespa)
En his treaty Petit traité montrant que c’est que doit faire un homme fidèle connaissant la vérité de l’Evangile, quand il est entre les papistes (1543), John Calvin defines what he means by nicodemism. For him, the Nicodemites are hypocrites, cowards, idolaters and individuals who force the meaning of the Scriptures to legitimize their behavior. He exhorts them to follow the path of odedience to God, martyrdom o exile in Geneva. For Calvin, one can not be Catholic and Reformed at the same time, but one or the other.